A rare case of primary penile leiomyosarcoma: A case report (Indian Journal of Case Reports, 2021)
Primary penile leiomyosarcoma is a rare tumor and very little data are available in the medical literature related to its behavior and potential outcome. A good surgical approach is essential for better disease-free survival. In our case study, a 50-year-old male presented with a 3-month history of penile swelling. The patient was treated with conservative surgery and immunohistochemistry played a key role in its diagnosis. No adjuvant therapy was given and the patient presented with a good surgical outcome after 6 months of follow-up. We present here a case report of this rare entity along with a short review of the literature including all the differential diagnoses of penile spindle cell lesions.